Diagnostic methods for feline coronavirus: a review - Sharif, Saeed; Arshad, Siti Suri; Bejo, Mohd Hair; Omar, Abdul Rahman; Allaudin, Zeenathul Nazariah; Alazawy, Amer (SAGE-Hindawi Access to Research, 2010)
Feline coronaviruses (FCoVs) are found throughout the world. Infection with FCoV can result in a diverse range of signs from clinically inapparent infections to a highly fatal disease called feline infectious peritonitis (FIP). FIP is one of the most serious viral diseases of cats. While there is neither an effective vaccine, nor a curative treatment for FIP, a diagnostic protocol for FCoV would greatly assist in the management and control of the virus. Clinical findings in FIP are non-specific and not helpful in making a differential diagnosis. Haematological and biochemical abnormalities in FIP cases are also non-specific. The currently available serological tests have low specificity and sensitivity for detection of active infection and cross-react with FCoV strains of low pathogenicity, the feline enteric coronaviruses (FECV). Reverse transcriptase polymerase chain reaction (RT-PCR) has been used to detect FCoV and is rapid and sensitive, but results must be interpreted in the context of clinical findings. At present, a definitive diagnosis of FIP can be established only by histopathological examination of biopsies. This paper describes and compares diagnostic methods for FCoVs and includes a brief account of the virus biology, epidemiology, and pathogenesis.